Endometrioid Adenocarcinoma Arising in Adenomyoma in a Woman with a Genital Prolapse - Case Report - Antovska, Vesna; Krstevska, Iskra; Trajanova, Milka; Chelebieva, Jasmina; Gosheva, Irena; Zdravkovski, Panche; Kostadinova Kunovska, Slavica; Janevska, Vesna (Scientific Foundation SPIROSKI, 2018)
BACKGROUND: Endometrial cancer is the third-ranked genital malignancy in women and includes 3% of cancer deaths. There is a 2.8% chance of a woman developing endometrial cancer during her lifetime. Low-grade endometrioid adenocarcinomas are often seen along with endometrial hyperplasia, but high-grade endometrioid adenocarcinomas have more solid sheets of less-differentiated tumour cells, which are no longer organised into glands, often associated with surrounded atrophic endometrium.CASE REPORT: We present an unusual case of endometrial adenocarcinoma arising in adenomyoma in 74-year old woman presented with genital prolapse, without other clinical symptoms. Ultrasound evaluation revealed endometrium with 4 mm-thickness and atrophic ovaries. The cervical smear was normal. The patient underwent a total vaginal hysterectomy. The histopathology of the anterior uterine wall revealed an intramural adenomyoma of 4 mm in which some endometrial glands with malignant transformation of well-differentiated endometrioid adenocarcinoma without infiltration in surrounding myometrium and lymphovascular invasion were present. The endometrium lining the uterine cavity was predominantly atrophic, and only one focus of simplex and complex hyperplasia was found, with cell-atypia. According to AJCC/FIGO 2010, the tumour was classified: pTNM = pT1B pNX pMX G1 R0 L0 V0 NG1, Stage I. On dismiss, the near-future oncological consultation was recommended.CONCLUSION: We would like to point out the rare occurrence of such type of malignancy and the importance of meticulous histopathology evaluation, even after reconstructive surgery for genital prolapse.
Keywords: endometrial cancer; adenocarcinoma; hyperplasia